Genuine articles : authentic reading texts for intermediate students of american english, student's book - Walter, Catherine (Cambridge : London : Cambridge University Press, 1986)
The Teacher's Manual provides specific guidance for using the book in class; ideas for warm-up activities; detailed suggestions for follow-up work in writing; vocabulary and oral fluency; and an answer key.
Keywords: English language -- Textbooks for foreign speakers; Readers; English language -- Study and teaching -- Foreign speakers